Observations on sound production in the Anatidae - Johnsgard, Paul A (Wildfowl, 1971)
A comparison of inter-species variations in the tracheal anatomy and acoustical characteristics of anatid vocalizations supports the contention that the trachea serves as a resonating tube, thus allowing for differential amplification of the syrinx-generated fundamental sound frequencies and their associated harmonics. The trachea apparent acts acoustically like an open-pipe, rather than a close-pipe, resonating instrument. Species having longer tracheal tubes seem to exhibit a greater degree of tracheal tuning effects and more ability to resonate lower sound frequencies than can species having shorter tracheal tubes. The extreme elongation of some species’ tracheal tubes by convolution, as found in the genera Anseranas and Cygnus, is a functional acoustic adaptation for long-distance communication by low-frequency sounds. The evolution of tracheal bullae by males of most Anatinae species is a method of ’emancipating’ the male sex from the relatively uniformly low-pitched and harmonic-rich calls of female ducks. Male courtship calls thus acquire greater species-specificity as well as relatively harmonic-free tones, and are primarily uttered in social situations at short distances.